PEMBELAJARAN BERBASIS MEDIA DIGITAL PADA ANAK USIA DINI DI ERA SOCIETY 5.0 - Ngatmin Abbas; Mar’atus Sholihah; Muhammad Syafe’i; Maharani; Fatin Aida Dzakia (LPPM IAD Probolinggo, 2025)
The development of digital technology in the Society 5.0 era demands a transformation in educational approaches, including early childhood education. This study aims to explore the role of digital media in supporting more effective learning experiences for young children. The method used is library research, involving a review of relevant literature to gain a comprehensive understanding of the topic. Findings reveal that digital media can provide interactive, personalized, and collaborative learning experiences. Educational platforms like ABCmouse and Khan Academy Kids offer engaging content through games and stories, helping children understand foundational concepts in enjoyable ways. However, challenges such as concerns over screen time and the quality of digital content also emerge. Therefore, the active role of educators and parents is crucial in supervising and selecting appropriate media. With thoughtful and well-directed use, digital media can serve as an effective educational tool to support children's cognitive, social, and emotional development. Keywords: Digital Media; Early Childhood; Learning; Society 5.0